OPTICAL-ELECTRONIC COMPLEX OF DETAILED SURVEILLANCE - Denisov, A; Popov, V V; Logunov, S V; Karev, P V (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2020)
Subject of Research. The paper presents algorithms and methods of the optoelectronic complex operation for detailed surveillance in space aimed at the search, detection and registration of spacecraft images withdrawn from service due to the expiration of the service life, as well as asteroids and space debris. Optical-electronic system consists of optical- electronic equipment that includes space review instrument, equipment of space debris visual identiﬁcation, equipment of stereoscopic detailed surveillance, as well as television laser system for building three-dimensional “cloud of points” (depth map) of the identiﬁed object. Method. Based on the analysis of known publicly available sources for space systems, we proposed a novel method that provides increasing the range to the object under study by conserving the pulse energy. The method gives the possibility to concentrate energy in a narrow angle due to the three precision motors in the developed device displacing the emitter installed on them. The proposed approach provides for three-planed control of the width and angle of the laser radiation. The original operation algorithms of the detailed surveillance optoelectronic complex for building a depth map of the object under study were developed. Main Results. The project of optoelectronic complex has been developed functioning in low, medium and geostationary orbits with the maximum relative linear velocity from the object under study up to 1.5 km/s in low and medium orbits, and up to 6.15 km/s in geostationary orbits. An original method of aiming the light beam at the object of observation has been developed. Practical Relevance. Applying the proposed algorithms, optical-electronic system of detailed surveillance draws a three-dimensional image of the observation object on distances from 100 m with the aim of its identiﬁcation and cataloguing. The results of the work can be useful in the development of laser systems, control systems for spacecraft rendezvous and docking, as well as for tasks with systems of spacecraft orbital maintenance for the military and civil industries.